Ability to Interpret Concentration of Statistical Data in the Form of Diagrams in Class VII Students of SMP Negeri 1 Boyan Tanjung - Rocalina, Nita; Yusmin, Edy; Ahmad, Dian; Halini, Halini; Hartoyo, Agung (Sean Institute, 2023)
The aim of this studyto explain and analyze the ability to interpret the concentration of statistical data in the form of diagrams in class VIII students at SMP Negeri 1 Boyan Tanjung.This study used descriptive qualitative method.The subjects in this research were 3 class VIII students at SMP Negeri 1 Boyan Tanjung. These 3 students were selected based on the results of a test on their ability to interpret the concentration of statistical data in diagram form and on the recommendation of the mathematics teacher at SMP Negeri 1 Boyan Tanjung.Students do not have difficulty understanding the data or statistical information provided, this is shown in questions 1 and question 2 which are from the test resultsIt shows that on questions 1 and 2 as many as 30 students (100%) could do well.Many students are inaccurate in changing information from problems into other forms, this is shown in question 3 where the test results areon question 3, 10 students (33.33%) worked on the question using the average formula with correct results.Many students cannot determine the solution or outcome of the problem, this is shown from question 4 as many as 7 students (23.33%) worked on questions using the median formula with correct results.